Optimising Mental Health in a Virtual World – Connecting from a Distance: College of Psychiatrists of Ireland Medical Student and Intern Essay Prize 2021 Runner Up - O'Rourke, Niall (Trinity Student Medical Journal, 2022)
• The use of modern technology and virtual approaches to mental health therapy is growing in importance across a diverse range of disorders. • While existing mental health therapies have been successfully adapted to virtual modes of delivery, modern technology is also driving exciting novel therapies. • Studies suggest virtual approaches to mental health care have both advantages and disadvantages. Further study and a cautious, evidence-based approach is key. • The complex and co-morbid nature of psychiatry means that patients will continue to require assessment and management by specialists. Virtual therapies are useful components of a stepped-care model, however patients with severe mental health problems will continue to require in-person care.